ASUHAN KEBIDANAN CONTINUITY OF CARE DI PMB EVA SAFITRI, CANDI SIDOARJO - Syu'bah, Afinatus; Rosyidah, Rafhani (Universitas Muhammadiyah Ponorogo, 2024)
In East Java, especially in Sidoarjo District, the maternal mortality rate in 2022 was 68.90 per 100,000 live births. This figure increased when compared to the realization in 2021, which was 59.69 per 100,000 live births. The highest maternal mortality rate is in the Candi Health Center working area, this occurs because the risk screening carried out on pregnant women is not optimal, including the competence of health workers in handling maternal emergencies and back referrals. Data collection techniques based on subjective and objective data obtained through interviews and direct physical examination. Total midwifery care in pregnancy was 2x because the mother had entered the third trimester, delivery 1x visit, postpartum period 2x visits, LBW 2x visits and family planning 1x visit. At the first visit of pregnancy the mother complained of tightness that was not accompanied by pain, at the second visit the mother complained of lower abdominal pain. In labor care, the mother came with an opening of 4cm with intact amniotic fluid, the baby was born at 13.30 WIB, the delivery process went normally in accordance with the standards of Normal Labor Care (APN). In the postpartum period, the first visit was carried out 6 hours postpartum with maternal complaints of suture wound pain and breast milk still coming out a little, at the second visit the postpartum period was found that breast milk production had increased. The mother has chosen to use IUD contraception which according to the client is a practical long-term contraception because it does not need to be remembered every day. This Continuity Of Care midwifery care takes place physiologically and there is no gap between theory and case.